Improving the Quality of 5 Feet Knife Sharing in Subsi Grinder with Seven Quality Control Tools (Case Study at PT KUTAI TIMBER INDONESIA) - Slamet, Moch.; Haryono (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2024)
In the face of the globalization era that is increasingly competitive, a company is required to be able to devise competitive in order to survive and win the competition. Because it needed a solution to improve the quality of the product so that it can assist in winning the competition with its competitors. PT. Indonesia Timber Kutai (ITC) as a company engaged in lumber and plywood production was should be able to survive in an increasingly tight competition. Plywood is formed by layers of sheets- sheets of wood called veneer. The quality of the veneers will effect the quality of plywood produced by PT Indonesia Timber Kutai. To get a good veneer quality then needed a good combination between the blade with the machine. Researchers do research on the condition of the blade. A place for pengashan blade is subsi Grinde The cause of the majority of the knife is a blunt knife quickly, so the quality of the produced veneer would be ugly. Researchers try to find problem  problems encountered an immediately make the effort improved sharpening results with seven quality control. For the results of his research is before there is an improvement obtained 22 case knife quickly dulled from 72 blade, after no improvement, found only 1 case of only fast knife dulled from 72 blades.